Yet another key learning point in the quest universal cartilage repair and restoration - Murrell, William D. (Annals of Translational Medicine, 2017)
One of the greatest challenges that continue to confront orthopaedic surgeons today is the management of large osteochondral defects of the knee. Despite great advances made in the last 3 decades, a well-defined, complete, and easily applied solution has not yet been demonstrated. Use of osteoarticular allograft is one such proposed solution that has been used since the 1980s with variable reported success (1). With clinical experience it became quickly apparent that the viability of both bone as well as chondrocytes was vital for radiographic incorporation and clinical success (1). The observation that short-term clinical experience quickly influenced the shift of using frozen osteochondral allograft (OCA) to fresh is supported by the exclusivity of studies fresh OCA investigations published to date. It was probably not the intent of the authors to highlight that use of decellularized OCA (DOCA) would be associated with high failure, but simply to report and inform. The groups’ findings demonstrated a clinically important distinction that the use of acellular grafts in an already compromised recipient is probably not judicious.